The influence of periodical, interference laser micromachining on nano-crystallization of amorphous magnetic ribbons - Ostrowski, Roman; Kusiński, Jan; Czyż, Krzysztof; Rycyk, Antoni; Sarzyński, Antoni; Skrzeczanowski, Wojciech; Strzelec, Marek; Czyż, Olaf (Photonics Letters of Poland, 2017)
The main problem connected with crystallization of amorphous magnetic materials from the FeSiB(X) group is the increase of their fragility with the increasing content of crystalline phase. To overcome this defect the possibilities offered by the interference, pulse laser heating of FeSiB ribbons were utilized. A simple, interference prismatic system at the output of Nd:YAG laser (8-10 ns, 2 J, 1064 nm) was used. The investigations included the influence of laser radiation energy density, number of laser pulses and their periodical, spatial surface arrangement on the crystallization process. Full Text: PDF References Y.R. Zhang and R.V. Ramanujan, "A study of the crystallization behavior of an amorphous Fe77.5Si13.5B9 alloy", Mater. Sci. Eng. A 416, 161 (2006). CrossRef T. Alam, T. Borkar, S. Joshi, S. Katakamb, X. Chenc and N.B. Dahotre, "Influence of niobium on laser de-vitrification of Fe-Si-B based amorphous magnetic alloys", J. Non-Cryst. Solids 428, 75 (2015). CrossRef K.G. Pradeep, G. Herzer, P. Choi and D. Raabe, "Atom probe tomography study of ultrahigh nanocrystallization rates in FeSiNbBCu soft magnetic amorphous alloys on rapid annealing", Acta Mater. 68, 295 (2014). CrossRef S. Katakam, J.Y. Hwang, H. Vora, S.P. Harimkar, R. Banerjee and N.B. Dahotre, "Laser-induced thermal and spatial nanocrystallization of amorphous Fe-Si-B alloy", Scr. Mater. 66, 538 (2012). CrossRef J. Kusiński, A. Sypień, G. Kusiński and C. Nilson, "Microstructure and nanochemistry of Ca-doped cobalt oxide single crystals", Mat. Chem. Phys. 81, 390 (2003). CrossRef C. Smith, S. Katakam, S. Nag, X. Chen, R.V. Ramanujan, N.B. Dahotre and R. Banerjee, "Improved soft magnetic properties by laser de-vitrification of Fe-Si-B amorphous magnetic alloys", Mater. Lett. 122, 155 (2014). CrossRef Ch. Lu and R. H. Lipson, "Interference lithography: a powerful tool for fabricating periodic structures", Laser Photonics Rev. 4, 568 (2010). CrossRef K. Czyż, J. Marczak, R. Major, A. Mzyk, A. Rycyk, A. Sarzyński and M. Strzelec, "Selected laser methods for surface structuring of biocompatible diamond-like carbon layers", Diam. Relat. Mater. 67, 26 (2016). CrossRef A. Sarzyński, J. Marczak, M. Strzelec, A. Rycyk, K. Czyż and D. Chmielewska, "Laser micro-structuring of surfaces for applications in materials and biomedical science", Proc. SPIE, 10159, 101590A (2016). CrossRef